Abstract 4350: Pharmacodynamic biomarker modulation by OMX-0407, a novel, spectrum-selective kinase inhibitor for the treatment of angiosarcoma and renal cell carcinoma - Marisa Stebegg-Wagner; Ilona Petra Maser; Bettina Bauer; Andreas Schirmer; Moritz Zulley; Carmen Amerhauser; Thorsten Meyer; Tiantom Jarutat; Hannes Loferer; Stefan Bissinger (Cancer Research, 2025)
Background: OMX-0407 is an orally available spectrum-selective kinase inhibitor targeting a set of oncology-relevant tyrosine kinases (TK) as well as the salt-inducible kinase (SIK) family, demonstrating a dual mode of action (MoA) in cancer. This involves OMX-0407-induced cell cycle arrest in tumor cells by de-phosphorylation and inactivation of TKs such as Src family kinases (SFK) and the SIK family, and increased sensitivity of the tumor microenvironment to immune-mediated tumor cell killing. OMX-0407 is currently undergoing early clinical testing for the treatment of angiosarcoma (AS) and clear cell renal cell carcinoma (ccRCC) (NCT05826600). Methods: Kinase activity profiling using the PamChip® kinase array was used to quantify OMX-0407 treatment effects. Moreover, a flow-cytometry-based “phosFlow” assay was developed to assess the phosphorylation status of SFKs. Both assays revealed dose-dependent inhibition of SFK phosphorylation and activity in peripheral blood mononuclear cells (PBMCs). Hence, they were implemented as pharmacodynamic biomarkers in the ongoing first-in-human trial (NCT05826600) of OMX-0407 in patients with previously treated unresectable solid tumors. Results: As of 30th of October 2024, 24 patients have received continuous treatment with OMX-0407 administered orally in 28-day cycles in a dose escalation study at dose levels of 10, 30, 60, 90, 100, and 140 mg twice daily (BID). Treatment was well tolerated with the main safety finding being gastro-intestinal adverse reactions. One patient with secondary radiation-induced angiosarcoma achieved a complete response at doses of up to 60 mg BID, which remains ongoing at 14 months. PhosFlow analysis confirmed OMX-0407 effects on the phosphorylation of SFKs in PBMCs at doses of 60mg and above. This was associated with the inhibition of oncology-relevant TKs as determined by functional kinase activity profiling. Treatment effects were significantly correlated with PK exposure. This confirms that both phosFlow and kinase activity profiling successfully resolve dose-dependent OMX-0407 activity in peripheral patient blood as pharmacodynamic biomarkers. These findings, together with safety findings and PK profiling, contributed to the selection of 100mg BID as the recommended phase 2 dose (RP2D) for the dose expansion. Conclusions & Outlook: OMX-0407 is a promising therapeutic candidate for the treatment of angiosarcoma and RCC with a potential dual MoA combining direct anti-tumor effects with modulation of the immune cell compartment towards a pro-inflammatory state. In September 2024, Ph1b expansion cohorts of the first-in-human trial (NCT05826600) were initiated for patients with unresectable/metastatic AS or ccRCC who have received at least one prior line of therapy, evaluating OMX-0407 at a dose of 100mg BID. Citation Format: Marisa Stebegg-Wagner, Ilona Petra Maser, Bettina Bauer, Andreas Schirmer, Moritz Zulley, Carmen Amerhauser, Thorsten Meyer, Tiantom Jarutat, Hannes Loferer, Stefan Bissinger. Pharmacodynamic biomarker modulation by OMX-0407, a novel, spectrum-selective kinase inhibitor for the treatment of angiosarcoma and renal cell carcinoma [abstract]. In: Proceedings of the American Association for Cancer Research Annual Meeting 2025; Part 1 (Regular Abstracts); 2025 Apr 25-30; Chicago, IL. Philadelphia (PA): AACR; Cancer Res 2025;85(8_Suppl_1):Abstract nr 4350.